Analisis Informasi Citra Anatomi Antara Penggunaan Aplikasi Constance Level Appearance (CLEAR) dan Non CLEAR Pada Pemeriksaan MRI Cervical Irisan Sagital T2WI FSE Kasus HNP - Dea Febri Mardiyanti; Sugiyanto Sugiyanto; Yeti Kartikasari (Poltekkes Kemenkes Semarang, 2015)
Background: This study aims to determine the anatomical image information between using CLEAR aplication and without CLEAR (Non CLEAR) aplication on cervical MRI examination with T2WI FSE sagital HNP case and to determine which is the best image between using CLEAR aplication and Non CLEAR aplication on cervical MRI examination with T2WI FSE sagital HNP case.Methods: This research was a quantitative research with an experimental approach Subjects of this study were eight patients in Siloam Lippo Village Hospital. Images resulted was assessed by radiology physician using questionnairs. Data were analyzed using Wilcoxon test to determine differences of image information and using mean rank test to determine the best image between using CLEAR application and without CLEAR aplication.Results: This study showed that there were differences anatomical image information between using CLEAR application and without CLEAR aplication on cervical MRI examination with T2WI FSE sagital HNP case, with p = 0,000 (p value 0,05). Cervical MRI examination with CLEAR aplication T2WI FSE produced the best image with the sum of the rank was 300,00 on the negative rank which showed that the image information without CLEAR aplication T2WI FSE lower than image information with CLEAR aplication T2WI FSE.Conclusion: There were differences the anatomical image information between using CLEAR application and without CLEAR aplication on cervical MRI examination with T2WI FSE sagital HNP case.